New Records of Cubozoan and Scyphozoan Jellyfish from Sabah Waters, Malaysia - Chee, Hoe Chuan; Balu Alagar Venmathi Maran; Tzuen, Kiat Yap; Kai, Ching Cheong; Muhammad Ali Syed Hussein; Ejria Saleh (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
Jellyfish play a vital role in the ocean’s ecosystem, acting as a nursery for young fishes, crabs, and brittle stars, as well as a source of food for certain charismatic megafauna, such as sunfish and sea turtles. They also pose a threat to human activities, with jellyfish blooms negatively impacting fisheries, power generation, and tourism. However, very little information is available on the biodiversity of jellyfish within the waters of Borneo. Here, we present new records of jellyfish found along the coast of Sabah, Malaysia, located in northern Borneo, bordering the megadiverse region of the Coral Triangle. A total of six species belonging to two classes and six families hitherto not recorded to the state are reported, Chironex yamaguchii, Acromitus maculosus, Crambione mastigophora, Linuche aquila, Netrostoma sp., and Phyllorhiza punctata. Of these, two species (C. yamaguchii and L. aquila) are harmful to humans, with C. yamaguchii capable of causing human fatalities. Reports of harmful jellyfish are useful to the medical and tourism industry, as some of these species may inflict stings and adverse reactions to humans ranging from rashes and skin irritation to fatal envenomation. A checklist has also been provided for all collected jellyfish species from Sabah waters of Borneo, Malaysia.